Health-related characteristics of Cancer survivors according to body mass index: a secondary data analysis - In Hoe Ku; Sangjin Ko (BMC Cancer)
Abstract Background Lifestyle habits and genetic factors of cancer survivors can lead to recurrence or development of new cancers. Obesity in cancer survivors increases the risk of cancer recurrence and affects mortality. This study aimed to analyze the relationship between health-related characteristics and related factors in cancer survivors by classifying obesity according to body mass index. Methods This study is a secondary data analysis research study using 5-year data, including 3-year (2016–2018) and 2-year data (2019–2020) from the 7th and 8th Korea National Health and Nutrition Examination Survey, respectively. This study targeted 4,553,669 cancer survivors who had completed past or early cancer management, did not have active cancer, or were receiving treatment for advanced cancer but were not in the terminal stage. Data were analyzed with complex sample descriptive statistics, cross-tabulation analysis and chi-square test and t-test. Lastly, complex sample multivariable linear regression analysis using IBM SPSS software. Results Demographic factors such as gender (t = -4.07, p <.001), marital status (t = 4.20, p <.001), and economic activity (t = -3.27, p =.002); health factors such as hypertension (t = 9.07, p <.001) and hemoglobin level (t = 5.29, p <.001); and nutrition-related characteristics such as frequency of breakfast (t = -6.49, p <.001), sodium intake (t = 2.41, p =.17), vitamin D intake (t = 3.02, p =.003), and vitamin C intake (t = -3.43, p =.001) were significant factors influencing cancer survivors’ BMI. Conclusions The results of this study are significant as they confirm the relationship between health-related characteristics and BMI in cancer survivors. The study comprehensively identified and presented various factors related to BMI in the lives of cancer survivors. To control BMI in cancer survivors, it is necessary to assess risk factors and change health behaviors and eating habits. Based on these results, developing and applying health intervention programs to prevent BMI increases and managing obesity in cancer survivors is essential. Promoting health strategies and studying the relationship with BMI in the future will contribute to increasing the healthy survival rate of cancer survivors.